L’expert en sinistre de l’avenir - Laguë, Luc (Assurances)

(untitled) (HEC Montréal, 1994)
The author profiles the loss adjuster, what this profession was like in the 60s and 70s and the qualities it takes to be a loss adjuster today–competence, versatility and a good knowledge of both technical and administrative aspects of the job. He then imagines the loss adjusters of the future: thoughtful, innovative and independent specialists with a solid professional training.